0058 Colorectal cancer risk and shift work in a population-based case-control study in Spain (MCC-Spain). (23rd June 2014) - Papantoniou, Kyriaki; Kogevinas, Manolis; Martin Sanchez, Vicente; Moreno, Victor; Pollan, Marina; Moleón, Jose Juan Jimenez; Ardanaz, Eva; MAltzibar, Jone; Peiro, Rosana; Tardon, Adonina; Alguazil, Juan; Navarro, Carmen; et al.
Abstract : Objectives: Epidemiological cancer studies on shift work have focused on breast cancer while evidence on other tumours is limited. We evaluated colorectal cancer risk in relation to night and rotating shift work and genetic variation, in a population based case-control study in Spain. Method: 1066 male and 592 female incident colorectal cancer cases and 3388 randomly selected population controls of both sexes, enrolled in 11 regions of Spain, were included. Information was collected on socio-demographic, lifestyle, medical history and other variables by face-to-face interviews. Lifetime occupational history on daily time schedule of each job, day/night/rotating shifts, light at night exposure, and duration of different jobs, was used for exposure assessment. We used unconditional logistic regression adjusting for potential confounders. Results: Among controls 10% of males and 4% females had ever worked full time in permanent night shifts (working between midnight and 6am) and 24% of males and 14% of females in rotating shifts for ≥1 year. Having ever performed rotating shift work was associated with an increased risk for colorectal cancer (adjusted Odds Ratio 1.33, 95% CI 1.15–1.55) compared to permanent day workers. ORs increased with cumulative years of rotating shift work and the OR for more than 30 years work 1.54 (1.22–1.94). Having ever worked in permanent night shift was not associated with colorectal cancer risk. Analysis on gene-environment interactions with genes in circadian, melatonin and sleep pathways are ongoing and will be presented. Conclusions: In this large population based study we found an increase in colorectal cancer risk associated with rotating shift work.